Simultaneous bioanalysis and pharmacokinetic interaction study of acebrophylline, levocetirizine and pranlukast in Sprague–Dawley rats. (1st September 2019) - Lohar, Priyanka; Sharma, Manish Kumar; Sahu, Amit Kumar; Rathod, Rajeswari; Sengupta, Pinaki
Abstract: The combination of acebrophylline (ABP), levocetirizine (LCZ) and pranlukast (PRN) is used to treat allergic rhinitis, asthma, hay‐fever and other conditions where patients experience difficulty in breathing. This study was carried out with the aim of developing and validating a reverse‐phase high‐performance liquid chromatographic bioanalytical method to simultaneously quantitate ABP, LCZ and PRN in rat plasma. The objective also includes determination of the pharmacokinetic interaction of these three drugs after administration via the oral route after individual and combination treatment in rat. Optimum resolution between the analytes was observed with a C18 Kinetex column (250 mm × 4.6 mm × 5 μm). The chromatography was performed in a gradient elution mode with a 1 mL/min flow rate. The calibration curves were linear over the concentration range of 100–1600 ng/mL. The intra‐ and inter‐day precision and accuracy were found to be within acceptable limits as specified in US Food and Drug Administration guideline for bioanalytical method validation. The analytes were stable on the bench‐top (8 h), after three freeze–thaw cycles, in the autosampler (8 h) and as a dry extract (−80°C for 48 h). The statistical results of the pharmacokinetic study in Sprague–Dawley rats showed a significant change in pharmacokinetic parameters for PRN upon co‐administration of the three drugs.